2021
DOI: 10.1108/ijoes-06-2021-0130
|View full text |Cite
|
Sign up to set email alerts
|

The effect of talent management and human capital on sustainable business performance: an empirical investigation in Malaysian hospitals

Abstract: Purpose This paper aims to examine the mediating role of human capital on the talent management in hospitals’ sustainable business performance in the health-care sector of Malaysia. Design/methodology/approach The study used a quantitative approach, with an initial sample of 174 Malaysian hospitals. The theoretical framework was based on previous studies of talent management (TM), human capital (HC) and sustainable business performance (SBP). Partial least squares-structural equation modelling (PLS-SEM) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 123 publications
1
7
0
1
Order By: Relevance
“…Motivating, engaging, and retaining employees are some of the most important aspects of an organization (Mures , an et al 2021;Werner 2021). A few studies on HR have responded to the worldwide COVID-19 crisis (AlQershi et al 2021;Aguinis and Burgi-Tian 2021;Delibasic et al 2021;Hitka et al 2021;Nayal et al 2022;Tamunomiebi and Worgu 2020;Watson 2022). Since most workers are now required to work remotely, the management of distance and boundary has become the primary focus of HR.…”
Section: How Fintech Enterprises Can Motivate Their Employeesmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivating, engaging, and retaining employees are some of the most important aspects of an organization (Mures , an et al 2021;Werner 2021). A few studies on HR have responded to the worldwide COVID-19 crisis (AlQershi et al 2021;Aguinis and Burgi-Tian 2021;Delibasic et al 2021;Hitka et al 2021;Nayal et al 2022;Tamunomiebi and Worgu 2020;Watson 2022). Since most workers are now required to work remotely, the management of distance and boundary has become the primary focus of HR.…”
Section: How Fintech Enterprises Can Motivate Their Employeesmentioning
confidence: 99%
“…There are extant literature reviews on TM (Aguinis and Burgi-Tian 2021). AlQershi et al (2021) examined the relationship between TM and sustainable business performance (SBP) even during COVID-19, as well as the challenges that confronted organizations. The result demonstrated that TM and performance exhibited a significant correlation (Aguinis and Burgi-Tian 2021).…”
Section: How Fintech Enterprises Can Motivate Their Employeesmentioning
confidence: 99%
“…Good motivation lies mainly in the correct behavior of the manager with employees, remuneration and creating conditions for work (Mulyani et al 2019). Previous research (Knapkova et al 2020;Morkoviciute and Edriulaitiene 2020;Paais and Pattiruhu 2020;AlQershi et al 2022) confirms that sufficiently motivated employees are more productive, more active, make sufficient investment in work, create higher value for work.…”
mentioning
confidence: 92%
“…The next issue is resistance to change, and public service employees may resist changes in their work practices, including changes that result from HR management training programs. Implementing new approaches and techniques can make it challenging (AlQershi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This will help to ensure that employees receive consistent and effective training programs. Overall, increasing investment in training resources, developing culturally and regionally relevant training programs, fostering a culture of continuous learning and development, raising awareness and understanding of sustainable public service administration, and encouraging collaboration and coordination among public service organizations are critical solutions to address the challenges facing HR management training approaches on sustainable public service administration skills in Indonesia (AlQershi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%